Аналіз практик кадрового забезпечення митних органів Польщі та Франції: адаптація до українських реалій - Колобиліна, О. О.; Kolobylina, O. O. (Вісник Харківського національного університету внутрішніх справ. – 2025. – № 1 (108), ч. 1. - С. 190-203, 2025)
Досліджено зарубіжний досвід кадрового забезпечення митних органів, зокрема Польщі та Франції, у контексті його адаптації до українських реалій. Проаналізовано ключові етапи реформ, серед яких зміна організаційної структури, конкурсні процедури, професійне навчання та оцінювання доброчесності кандидатів. Особливу увагу приділено багаторівневому підходу Франції та інтеграційним процесам Польщі. Запропоновано запровадити диференційований підхід до добору кадрів, посилити конкурсні процедури та створити систему професійного навчання. Зазначено, що використання європейського досвіду сприятиме модернізації митної служби України та її інтеграції до ЄС.

The article examines foreign experience in staffing customs authorities in the context of its adaptation to Ukrainian realities. Particular attention is paid to the analysis of the practices of Poland and France, which have successfully reformed their customs services in accordance with European standards. The key stages of the reforms, including transformation of the legislative framework, improvement of administrative procedures and introduction of modern approaches to personnel selection, are highlighted. The experience of Poland demonstrates the effectiveness of integration processes with the EU through changes in the organisational structure of customs authorities, reduction of the number of units and optimisation of staffing. Staff rotation, competitive procedures and the creation of conditions for professional training play an important role. Poland also actively uses administrative tools to assess the integrity of candidates and their qualifications. In France, on the other hand, the emphasis is on a multi-level competitive selection process that includes written tests, practical assessment, interviews, physical training and psychological assessment. Training in specialised institutions, such as the National Customs School in La Rochelle, plays an important role. A comparative study of the requirements for candidates in Poland and France has been conducted. While in Poland these requirements are moderate, in France they are much stricter and include knowledge of foreign languages, a high level of professional training and compliance with ethical standards. The experience of France in implementing multi-stage competitive procedures to select the best specialists is particularly valuable for Ukraine. In order to effectively reform the customs authorities of Ukraine, it is proposed to introduce a differentiated approach to recruitment, strengthen competition procedures, implement testing for knowledge of legislation and foreign languages, and thoroughly check the moral and ethical qualities of candidates. It is necessary to create a system of long-term professional training and internships that will allow new employees to effectively adapt to the specifics of the customs service. The comprehensive reform of Ukraine's customs service, taking into account European experience, will contribute to the modernisation of the State Customs Service of Ukraine and the country's integration into the European community.
An analysis of staffing practices of Polish and French customs authorities: adaptation to Ukrainian realities
Keywords: кадрове забезпечення; митні органи; міжнародний досвід; конкурсний відбір; професійне навчання; стажування; система заохочень; доброчесність; державна служба; Державна митна служба України; staffing; customs authorities; international experience; competitive selection; professional training; internships; incentive system; integrity; civil service; State Customs Service of Ukraine